In vitro ovicidal studies on egg-parasitic fungus Pochonia chlamydosporia and safety tests on mice - Ma, Yuan; Lv, Jinbao; Jiang, Lili; Fan, Zhaobin; Hao, Luyao; Li, Zhengyi; Ma, Chengyu; Wang, Rui; Luo, Hongliang (Frontiers in Veterinary Science, 2025)
IntroductionThe control of parasites infections in livestock is an ongoing concern, with parasites developing resistance to commonly used antiparasitic drugs. The current study investigated in vitro the destructive effect of the fungus Pochonia chlamydosporia on the eggs and oocysts of several equine parasites, as well as assessing the safety of the fungus in mice.MethodsS. equinus, P. equorum, Anoplocephala spp eggs and Eimeria spp. oocysts were treated with P. chlamydosporia. The prepared preparation was also administered to mice, and the physiological indexes and lesions of major tissues and organs, as well as pathological sections of tissue, were then observed.ResultsP. chlamydosporia exhibited varying degrees of efficacy in the control of S. equinus, P. equorum, Anoplocephala spp eggs and Eimeria spp. oocysts. The acute toxicity test demonstrated that there was no death or toxicity symptom observed in the mice, with no significant difference in clinical observations, such as respiration, mental state, appetite, or feces, between the control and treated mice after the feeding of the biological preparation of P. chlamydosporia.DiscussionThese findings suggested that administration of P. chlamydosporia would be safe to use in livestock and provided a rationale for its potential clinical application, pending further analyses.